1987
DOI: 10.1128/mcb.7.5.1646
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the integrant in MyK-103 transgenic mice in which males fail to transmit the integrant.

Abstract: Males in the transgenic mouse pedigree MyK-103, although fertile, do not transmit the integrant to offspring.The integrant is on chromosome 6 near the T-cell receptor D-chain locus. It contains four fragments of the plasmid pMK (a metallothionein-thymidine kinase fusion gene) and a 532-base-pair fragment of displaced mouse DNA originating from a previously uncharacterized repetitive DNA family. The integration complex is flanked on either side by a 5-kilobase duplication of mouse DNA normally found in a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
1
3

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 65 publications
2
67
1
3
Order By: Relevance
“…Such findings are a recurrent theme: many other investigators have found Topo I consensus sequences, and other sequences such as Escherichia coli CHI element and minisatellite sequences, near transgene-chromosome junctions. 43,44,59,94,95 It has been demonstrated that integration of a circular bent DNA-containing vector preferentially occurs at the bent site, while bent DNA structures are often found at illegitimate recombination junctions and rearrangement breakpoints. 76 This suggests that such bent DNA sites in the genome (which are numerous) might be involved in integration.…”
Section: Illegitimate Integration Sites Are Not Totally Randommentioning
confidence: 99%
See 1 more Smart Citation
“…Such findings are a recurrent theme: many other investigators have found Topo I consensus sequences, and other sequences such as Escherichia coli CHI element and minisatellite sequences, near transgene-chromosome junctions. 43,44,59,94,95 It has been demonstrated that integration of a circular bent DNA-containing vector preferentially occurs at the bent site, while bent DNA structures are often found at illegitimate recombination junctions and rearrangement breakpoints. 76 This suggests that such bent DNA sites in the genome (which are numerous) might be involved in integration.…”
Section: Illegitimate Integration Sites Are Not Totally Randommentioning
confidence: 99%
“…44 However, more complex insertion patterns are frequently observed (see Figure 2b). The recipient genomic locus can undergo extensive physical rearrangements at the site of integration, 45,50,51,58,59 including deletions (as much as tens of kb), duplications, and translocations, among others. 43,52,60 Another consequence is that the integrated material can interrupt coding sequences.…”
Section: Introductionmentioning
confidence: 99%
“…A duplication of the target is possible when the T-DNA integrates at a staggered nick or when integration occurs at breakpoints between sister chromatids within a replication bubble (see Fig. 5C), as postulated by Wilkie and Palmiter (1987). T-DNAs arranged in tandem or inverted repeats could be the consequence of end ligation of T-DNA copies before insertion, but the inverted repeats are more likely due to strand switching during repair at the T-DNA ends (Jorgensen et al 1987).…”
Section: Variations On the Modelmentioning
confidence: 99%
“…This suggests that integration occurs during DNA replication. Wilkie and Palmiter [48] have proposed that the free ends of the transgene initiate recombination by invading a replication "eye".…”
Section: Illegitimate Recombinationmentioning
confidence: 99%